INOVASI PEMADAM API DARI KULIT SINGKONG UNTUK MENUNJANG KEAMANAN PROSES PRODUKSI DI UMKM LUMPIA JENG NENNY - Widayat, Vereline Abigael; Permana, Yafi Elian; Kareem, Nafi; Nurdiansyah, Rudi; Mubarok, Zamruda Sariangi Sauqi; Karika, Sri; Azzahra, Prestika Dilla (Universitas Negeri Malang, 2024)
This community service program aims to improve the safety of the production process at the Lumpia Jeng Nenny micro/small/medium enterprises (MSMEs) located in Dusun Krajan, Sukorejo, Pasuruan, by developing a light fire extinguisher made from cassava skin (SIPAR: Singkong APAR). The methods used include location surveys, collecting data on partner needs, developing SIPAR products through preparation of materials and production processes, socialization and training of product use to partners. The development results show that SIPAR is not only able to extinguish fires in seconds, but is also environmentally friendly and of course safe for beginners. By implementing SIPAR, the